EP526 Inactivating mutations of the IK gene inhibit endometrial cancer progression through regulating mitosis and non-homologous end joining DNA repair pathway. (1st November 2019) - Gao, C; Jin, G; Wang, Y; Forbes, ME; Yan, Y; Tian, W; Mangala, LS; Sood, AK; Xue, F; Zhang, W
Abstract : Introduction/Background: IK is a mitotic factor that can promote cell cycle progression. Our recent investigation of the 271 endometrial cancer (EC) samples from The Cancer Genome Atlas (TCGA) dataset showed that IK gene mutations were strikingly enriched in cluster IV which consisted of most of the high grade and high stage patients and this cluster had better overall survival (OS). Therefore, we further characterized the roles of IK gene mutations and their coded protein in EC progression. Methodology: We used bioinformatics methods to analyze the somatic mutational types of IK gene and the relationship between IK mutation and OS rate of EC patients in the updated TCGA dataset (n=547). Somatic mutations for 30 DNA repair genes were called to analyze the mutation burdens of EC patients. In vitro and in vivo experiments were used to study whether and how IK influences the EC progression. All statistical tests were two-sided. Results: The most common somatic mutational type of IK was frameshift and this kind of inactivating mutations was unique for alive EC patients. TCGA data analysis showed that IK/Ku80 mutations caused higher mutation burdens of EC patients and they were associated with significantly better OS. IK attenuation led to enrichment of G2/M phase cells and inactivation of DNA repair signaling by inhibiting the heterodimerization of Ku80 and Ku70. In addition, IK attenuation sensitized EC to cisplatin treatment in vitro and in vivo. IK expressed higher in EC tissue and high IK expression was significantly associated with several clinicopathologic variables, such as age, hypertension, body mass index (BMI) and lymph node metastasis. High IK expression was negatively correlated with OS of EC patients. Conclusion: Inactivating mutations of the IK gene and loss of IK expression are likely to contribute to inhibit EC progression. IK can be considered as an effective therapeutic target against EC. Disclosure: Nothing to disclose.